Evaluating the Effectiveness of Office Administration Training Using the Kirkpatrick Model (Case Study at PT Supportindo Prima Mandiri) - Shinta Wulandari; Tajuddin Pogo (Indonesian Journal of Business Analytics, 2023)
This study aims to evaluate the effectiveness of office administration training from PT Supportindo Prima Mandiri using the Kirkpatrick model. The population of this study was comprised of alumni of office administrative training participants held by PT Supportindo Prima Mandiri, with a sample size of 70 people. Data analysis through SmartPLS with brainstorming techniques The results of this study indicate that office administration training has been going well. The results of the evaluation at each level were: (1) at level 1-reaction, the trainees showed positive reactions in the good category; (2) at level 2-learning, the trainees showed positive reactions in the good category; and (3) at level 3-behavior, they obtained training participants showed positive reactions in the good category.